How Do Board Structure and Risk Management Interact to Influence Derivative ‎Recognition Under IFRS-9 among African Banks?‎ - Oreoluwa , Akinadewo Jeremiah; Seriki , Akinadewo Israel; Isaiah, Oluwagbade Oluyinka; Abass , Jabar Adebola (International Journal of Accounting and Economics Studies, 2025)
This study examines the interaction between board structure and risk management in shaping ‎derivative recognition under IFRS 9 within African banks. Drawing on panel data from 73 banks ‎across multiple jurisdictions between 2012 and 2023, the analysis employs fixed effects regression ‎with Driscoll–Kraay standard errors to control for cross-sectional dependence and ‎heteroskedasticity. Board attributes are evaluated as determinants of derivative asset, liability, and ‎net derivative asset ratio, while risk management serves as a moderating variable reflecting ‎institutional capital adequacy and prudential control strength. The results indicate that larger and ‎more independent boards enhance compliance with IFRS 9 derivative recognition standards, but ‎their effects become more conservative in banks with stronger risk governance frameworks. ‎Gender diversity fosters prudence in liability classification, and board diligence influences net ‎derivative positions primarily when reinforced by structured risk oversight. The study provides ‎empirical evidence for aligning IFRS 9 implementation with Basel IV reforms and underscores the ‎need for capacity building, regulatory harmonisation, and risk-governance alignment to strengthen ‎financial transparency and stability across African banking systems.
Keywords: African Banks; Board Structure; Derivative Recognition; IFRS 9; Risk Management